2005
DOI: 10.1097/00003677-200510000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Physical Activity Environmental Correlates: Increased Specificity for Ecological Models

Abstract: Ecological models are now used to understand the complex array of factors that influence physical activity, resulting in a greater emphasis on environmental correlates. This selective review examines whether the predictive capacity of these models could be improved if behavior-specific measures of the environment were used to predict context-specific behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
466
1
16

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 569 publications
(517 citation statements)
references
References 12 publications
30
466
1
16
Order By: Relevance
“…Land use mix, composite walkability indices and neighborhood type were nevertheless consistently associated with higher physical activity levels even after controlling for neighborhood self-selection. Moreover, the built environment was found to be more supportive of walking and cycling compared with physical activity more generally-congruent with previous findings [10,24,25] and with current knowledge regarding behavior-specific environmental settings [61]. …”
Section: Discussionsupporting
confidence: 88%
“…Land use mix, composite walkability indices and neighborhood type were nevertheless consistently associated with higher physical activity levels even after controlling for neighborhood self-selection. Moreover, the built environment was found to be more supportive of walking and cycling compared with physical activity more generally-congruent with previous findings [10,24,25] and with current knowledge regarding behavior-specific environmental settings [61]. …”
Section: Discussionsupporting
confidence: 88%
“…Although slight, this additional gain in associations may be due to the contextspecificity of the measures. As suggested by Giles-Corti et al [54], when environmental measures more closely match with the setting in which the behavior takes place, the predictive capacity of the model improves. Interestingly, a relationship between perceived park quality and park-based physical activity during last visit did not emerge in this study.…”
Section: Discussionmentioning
confidence: 85%
“…Definitions of both neighborhood and parks were provided for respondents. Specifically, neighborhood was defined as "the area within a 10-to 15-min walk from your home" [53,54], and parks were identified as "a public park or outdoor recreation area in the community that is designed for active or passive use" [55]. This approach was chosen because respondents may not necessarily think of the park that we used to identify the census blocks for sampling as their neighborhood park, and it often was not their closest park.…”
Section: Methodsmentioning
confidence: 99%
“…Distance to sports facilities, neighbourhood characteristics and sports participation Despite theoretical agreement on the positive effect of sports facilities being available at an acceptable distance (Giles-Corti, Timperio, Bull, & Pikora, 2005;Sallis et al, 2006), empirical studies have shown mixed results regarding the influence of objectively measured accessibility and availability of sports infrastructure on sports participation, partly due to the use of different definitions 240…”
Section: Literature Review and Theorymentioning
confidence: 99%